Ricadute territoriali del decentramento universitario in area suburbana mediante analisi delle caratteristiche glocali delle università. Un approccio lefebvreriano - Daniela La Foresta; Stefano De Falco (Bollettino della Società Geografica Italiana)
The relationship between university and city over time has been subject to alternating phases, often also very controversial. In recent years, the theme relating to the push of the academic reality towards the territory has enriched the scientific debate making it now mature on this aspect. This paper explores the particular declination of this theme in the case of university decentralization in the suburban area, focusing critical analysis on local impacts and dynamics in relation to the glocal characteristics of the universities. The evaluation of the territorial impacts is developed in a Lefebvrerian perspective, epistemologically able to hold the city as an “urban society”, therefore, rich in social contradictions that the university must internalize, negotiating them in the best way. The characteristic of mediation, proposed by Lefebvre, is emphasized in the methodological proposed approach, firstly, on the basis of a review of the literature, identifying the most critical areas of the suburban areas that need regeneration and strengthening actions, and then placing the results  in relation to the glocal characteristics of the university, defined according to national and international standards. The theoretical approach has also been declined and characterized in the specific case of the eastern suburban area of Naples, site of a recent university decentralization and of a consequent establishment of Academy of the main multinationals in the high-tech sector, which lends itself to being a perfect real laboratory for analyzing the discussed phenomena and paradigms.